2011
DOI: 10.1007/s12013-011-9229-x
|View full text |Cite
|
Sign up to set email alerts
|

The Co-expression of USP22 and BMI-1 May Promote Cancer Progression and Predict Therapy Failure in Gastric Carcinoma

Abstract: Recent experimental evidence support the model in which the simultaneous induction of BMI-1 and USP22 is critical during cancer progression. Whether this model may affect gastric cancer (GC) progression is worthy of additional study. In this study, we examined the significance of the USP22 and BMI-1 expression in GC (n = 219), non-cancerous mucosa (n = 37), and lymph node metastasis (n = 37). The protein expression level of USP22 and BMI-1 were concomitantly up-regulated from non-cancerous mucosa to primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 24 publications
6
72
1
Order By: Relevance
“…Overexpression of BMI-1 has been previously reported in gastric, ovarian, breast, head and neck, pancreatic and lung cancer, as well as in primary hepatocellular carcinoma (HCC) and endometrial carcinoma (8)(9)(10)(11)(12)(13)(14)(15)(16). In addition, BMI-1 overexpression has been identified in patients suffering from myelodysplastic syndrome, chronic myeloid leukemia, acute myeloid leukemia and lymphoma (17)(18)(19)(20).…”
Section: Bmi-1 and Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…Overexpression of BMI-1 has been previously reported in gastric, ovarian, breast, head and neck, pancreatic and lung cancer, as well as in primary hepatocellular carcinoma (HCC) and endometrial carcinoma (8)(9)(10)(11)(12)(13)(14)(15)(16). In addition, BMI-1 overexpression has been identified in patients suffering from myelodysplastic syndrome, chronic myeloid leukemia, acute myeloid leukemia and lymphoma (17)(18)(19)(20).…”
Section: Bmi-1 and Cancermentioning
confidence: 97%
“…Epithelial-mesenchymal transition (EMT) is the key process driving cancer metastasis and BMI-1 has been demonstrated to induce EMT in endometrial carcinoma cells (28). Furthermore, in vivo studies revealed that BMI-1 expression was upregulated in cancer tissues compared with matched healthy tissues and was associated with distant metastases of gastric cancer (8,29), HCC (15), lung cancer (14,30,31), endometrial carcinomas (16,28,32), and head and neck cancer (11,12,33). Several previous studies have also suggested that BMI-1 contributed to mammary carcinogenesis, axillary lymph node metastases, highly aggressive behavior and late-stage relapse in breast cancer (6,10,(34)(35)(36).…”
Section: Bmi-1 and Cancermentioning
confidence: 99%
“…The USP cleavage assays used ubiquitin-met-β-galactosidase (Ub-Met-β-gal) and pGEX-Ub52 (GST-Ub52) (W. Zhang et al, 2011) as model substrates. Total protein extracts of the Ub-Met-β-gal group were analyzed by western blotting, and total protein extracts of the pGEX-Ub52 group were purified by glutathione agarose beads and detected by Coomassie Brilliant Blue.…”
Section: Deubiquitinating Enzyme Activity Assay Of Husp22mentioning
confidence: 99%
“…Elevated expression of USP22 can predict shorter intervals of tumor recurrence, distant metastasis, therapeutic failure and poor prognosis in patients with many types of cancer such as colorectal cancer (Liu et al, 2010(Liu et al, , 2011, breast cancer (Y. Zhang et al, 2011), gastric cancer and others (Ueda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As a component of the transcription regulatory histone acetylation complex SAGA, USP22 regulates gene transcription at an epigenetic level through the deubiquitination of histones, exerting broad biological functions, including cell cycle progression, embryonic development and telomere homeostasis (4)(5)(6). USP22 is expressed in numerous normal human tissues but is overexpressed in malignant tumors, such as colorectal, liver, breast, gastric, bladder and lung cancer, a showing correlation with tumor progression and metastasis (7)(8)(9)(10)(11)(12)(13)(14). Findings of these studies have demonstrated the importance of USP22 in cancer development; however, the role of USP22 in pancreatic cancer has not been investigated.…”
Section: Introductionmentioning
confidence: 99%